UNDERSTANDING LEARNERS’ INCONSISTENCIES WITH THE ‘O’ VOWEL AND ‘O-KAR’ IN BANGLA LANGUAGE - Ahsan, Mohd Twarique; Islam, Mohammad Torikul (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
Bangla, an Indo-Aryan language of the Indo-European family, employs an orthographic system where vowels are represented both as independent letters and diacritical marks. This dual representation introduces inconsistency and complexity in spelling and reading, particularly for young learners acquiring foundational literacy skills. A persistent challenge arises from the use of the O-Kar diacritic, which modifies consonants to produce the vowel /o/ sound, but is often omitted in certain lexical contexts, leading to inconsistencies in Bangla pronunciation and spelling. This study investigates the difficulties faced by native Bangla-speaking children in spelling and pronouncing words containing the inherent consonant O, especially when the O-Kar diacritic is absent. Data were collected through written assessments and structured interviews with 52 native Bangla-speaking children aged 8–11 from Berhampore, West Bengal. Three separate sets of word—each with 15 target words featuring inherent O consonant—were presented both with and without the O-Kar diacritic in the initial, medial, and final positions. Findings reveal significant spelling inconsistency when the diacritic was omitted, with learners frequently deviating from standard orthographic conventions. Conversely, words including the diacritical were consistently spelled and pronounced more accurately. This inconsistency persisted across all word positions, suggesting that the optional application of O-Kar impedes overall reading and writing fluency. The study highlights the need for standardized pedagogical approaches to mitigate spelling inconsistencies and improve literacy outcomes in Bangla. These findings have broader implications for Bangla phonological and orthographic conventions and are practically relevant to lexicographers, language education policymakers, and teachers.